Assessment of Health Risk due to Pesticide Residues in Fruits, Vegetables, Soil, and Water - Nikhat Khan; Ghazala Yaqub; Tahreem Hafeez; Madiha Tariq (Journal of Chemistry)
The present study was conducted to assess the contamination and health risk due to the presence of pesticides in fruits and vegetables. A total of six vegetable samples, 3 fruit samples, 7 soil samples, and 6 water samples were collected from three different sampling points. High-performance liquid chromatography using acetonitrile and water solvent system was employed for the quantitative and qualitative analysis. The pesticides having the highest health risk in vegetables were Bifenthrin and Difenoconazole as their health risk index was found to be exceeding the cut off value of 1. Imidacloprid was found in all vegetable samples but had no associated health risk, as all the health risk indices for imidacloprid were below the cut off value of 1. The pesticide Glyphosate detected in only one sample had no health risk associated with it. Health risks in fruits were the highest for Amamectin, Bifenthrin, and Difenoconazole and were crossing the threshold limit of 1. The results reveal the health risk indices of Bifenthrin and Difenoconazole range from 7.8 to 12.46 in vegetables and from 2.704 to 30.454 in fruits, hence, posing a serious threat to human health. Amamectin, although detected in only fruit and water samples, had the highest health risk of 30.454. Imidacloprid and Glyphosate found in every fruit sample had no associated health risk. The results revealed the presence of pesticides in water, soil, fruit, and vegetable samples. Consumers utilizing these vegetables and fruits are under potential health risks due to the presence of pesticides in soil and water. Practical Applications. In this study, an analytical method for detecting pesticides in a variety of environmental matrices including fruits, vegetables, water, and the soil is presented and the health risk associated with the presence of pesticides in a wide range of fruits and vegetables is assessed. It is highly significant because in developing countries agricultural activities contribute majorly toward the total gross domestic product and pesticides are extensively used to control, prevent, devastate, and diminish any harmful pest that destroys crops.